Metabolic control of patients with phenylketonuria in a portuguese metabolic centre comparing three different recommendations - Kanufre, Viviane (2021)
Funding Information: Conflicts of Interest: M.F.A. received grants from Glutamine, Nutricia, Merck Serono, Biomarin, Orphan and Lifediet to attend scientific meetings. A.M. has received research funding and honoraria from Nutricia, Vitaflo International and Merck Serono. She is a member of the European Nutritionist Expert Panel (Biomarin), a member of Sapropterin Advisory Board (Biomarin), a member of the advisory board entitled ELEMENT (Danone-Nutricia), and a member of an advisory board for Arla and Applied Pharma Research. A.P. received an educational grant from Cambrooke Therapeutics and grants from Vitaflo, Nutricia, Merck Serono, Biomarin, and Mevalia to attend scientific meetings. J.C.R. is a member of the European Nutritionist Expert Panel (Biomarin), the Advisory Board for Applied Pharma Research and Nutricia, and received honoraria as a speaker from APR, Merck Serono, Biomarin, Nutricia, Vitaflo, Cambrooke, PIAM and Lifediet. Funding Information: Funding: CINTESIS—UIDB/4255/2020 a program financially supported by Fundação para a Ciência e Tecnologia/Ministério da Educação e Ciência, through national funds is acknowledged. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.